Co3O4 nanocrystals with predominantly exposed facets: Synthesis, environmental and energy applications - Sun, Hongqi; Ang, Ha Ming; Tade, Moses; Wang, Shaobin (R S C Publications, 2013)
Facet-dependent properties of novel metal or metal-oxide nanocrystals were discovered recently, and are attracting intensive interest owing to their great potential for various practical applications. Co3O4 as an important transition metal oxide shows electronic, magnetic, and redox properties which have found many applications in energy conversion and storage, magnetic separation, sensor devices and catalysis. This review summarizes the most recent research advances in synthesis and applications of nanosized Co3O4 with predominantly exposed facets, with emphasis on the enhanced performances in catalysis and electrochemical properties. The mechanism for improved selectivity and activity was discussed, and a panorama of the correlations between particle shape, crystal plane, surface atom arrangement, and active sites has been drawn. Insightful findings in this scope may be achieved by forthcoming research in theoretical calculations, rational synthesis, and emerging applications. Thus, researchers can manipulate the synthesis at the atomic level resulting in novel applications of the materials in a wide variety of areas.